Lubuklinggau Merdeka Field As A Cultural Site Historical Land 1934 - 1988 - Berlian Susetyo; Muhammad Wahayuni (Criksetra: Jurnal Pendidikan Sejarah, 2022)
Efforts to save cultural heritage is something that must be done because it is the identity of a nation. Through this research, it will be explained how the Lubuklinggau independent field can be the basis for becoming a historical land cultural site. The purpose of the research is to explain the Lubuklinggau Merdeka Square as a historical land cultural site (1934-1988). The research method used is the historical method, with stages: heuristics, source criticism, interpretation, and historiography. The results showed that buildings or sites generally received less attention. Important historical buildings are generally located in city centers. Now the city center has been developed into a commercial area so that the cultural heritage in this area is very vulnerable to be demolished and replaced with shopping or tourist center buildings, such as Merdeka Square in Lubuklinggau City, South Sumatra Province. Therefore, this place is the location of events across the ages starting from the colonial period, the physical revolution period and the new order era.